The macro- and micro-prospects of the energy potential of the anaerobic digestion of corn straw under different storage conditions. (September 2019) - Zhao, Yubin; Yu, Jiadong; Zhao, Xiaoling; Zheng, Zehui; Cai, Yafan; Hu, Yuegao; Cui, Zongjun; Wang, Xiaofen
Abstract: This study demonstrated the efficiency of storage conditions for corn straw is very important in maintaining high methane production. Using data from lab-scale experiments with fresh, silage and dry corn straw, the relationships among the different materials, microbial changes and methane production were analyzed. Moreover, the economic evaluation of three different straw types was conducted. The results showed a cumulative methane production of 207 mL/g total solids (TS) for silage straw. This yield was 9.34% less than that of fresh straw and 17.08% more than that of dry straw. The silage straw with higher organic acids successfully reduced the loss of dry matter (DM) to 3.77%, and the loss of DM was 15.6% for dry straw. The dominant Spirochaeta, Treponema and Methanosaeta in silage straw were reasonable for high methane production. Furthermore, the economic evaluation suggested silage should completely replace traditional dry storage prior to anaerobic digestion in North China. Graphical abstract: Unlabelled Image Highlights: Silage reduced DM loss to 3.77% compared with a 15.6% increase for dry straw. Silage had a higher proportion of organic acids than water soluble carbohydrate. Spirochaeta, Treponema and Methanosaeta in silage were responsible for methane yield. Silage increased methane yield by 17% relative to dry storages. Silage has the most positive economic balance comparing with dry and fresh straw.